Advancing tuber crops research: New initiatives - Sreekumar, J; Mohan, C; Radhika, N Krishna; Makeshkumar, T (Indian Horticulture, 2025)
Tuber crops like cassava, sweet potato, yam, and aroids are vital for global food security, and their improvement is being revolutionized by genome editing, omics, and AI. Genome editing, especially CRISPR/Cas, enables precise trait modification for disease resistance, nutrition, and climate resilience. Omics technologies viz., genomics, metabolomics, and phenomics provide insights into genetic variation, biochemical pathways, and trait expression, while integrated multi-omics enhances predictive breeding and biomarker discovery. Traditional breeding remains essential but it is strengthened by these tools. AI and machine learning accelerate data integration, linking genotype to phenotype, predicting complex traits, and enabling climate-smart, resilient, nutritionally rich and highyielding tuber crop development.